Police Unions: contribution to a new system for representativeness assessment - Rego, Raquel (2021)
With the democratic transition that began in Portugal in 1974 the police, too, sought to organize into unions. But this aspiration was achieved only at the beginning of the 21st century, when the path to union proliferation was opened, with 19 organizations having been reached in 2019. This article shows that the instrumentalization of the legal form by the police led to the distortion of the nature of union action. Based on interviews and document analysis, we conclude that the assessment system of union representative- ness requires objective and predictable criteria to have minimum (not sufficient) conditions for social dialog.